Mrs. Sinclair's suitcase - Walters, Louise (Amy Einhorn Books, Published by G.P. Putnam's Sons, a member of Penguin Group (USA), 2014)
"Roberta is a lonely thirty-four-year-old bibliophile who spends her days working at The Old and New Bookshop in England. She has a habit of keeping the odds and ends she finds inside used books. So when her father comes to the store with a heap of secondhand books inside a battered suitcase that once belonged to Roberta's 109-year-old grandmother, Dorothea, she is intrigued. Inside the suitcase she discovers a letter addressed to Dorothea that hints at a dark secret. Curious to know more, Roberta sets out to uncover the truth, but what she learns upturns her understanding of her family's history completely."